Mechanism of isorhynchophylline in lipopolysaccharide-induced acute lung injury based on proteomic technology - Li, Yaru; Xing, Junfeng; Qin, Ling; Zhang, Chuanming; Yang, Zheng; Qiu, Min (Frontiers in Pharmacology, 2024)
Abstract Isorhynchophylline(IRN), a tetracyclic indole alkaloid, has anti-inflammatory and antioxidant activities against cardiovascular diseases and central nervous system disorders. Acute lung injury (ALI) is a manifestation of inflammation concentrated in the lungs and has a high incidence rate and mortality. Here, we established a mouse model of ALI and observed the effects of IRN. Proteomic results showed that 5727 proteins were detected in mouse lung tissues, and 16 proteins were screened out. IRN could reverse the trend of these differential proteins. In addition, IRN can act on integrin αM to reduce neutrophil recruitment and thereby produce anti-inflammatory effects and may suppress neutrophil migration through the leukocyte transendothelial migration pathway. Data are available via ProteomeXchange with identifier PXD050432. TUNEL and RT-PCR experiments revealed that LPS-induced ALI in mice increases the apoptosis of lung tissues, damage to alveolar epithelial cells and levels of inflammatory factors. Treatment with IRN can repair tissues, improve lung tissue pathology and reduce lung inflammation.